(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Philippines is one of the world’s most susceptible countries when it comes to disasters such as typhoons, floods, landslides, volcanic eruptions, earthquakes, etc. The Philippine government was able to come up with different adaptive strategies because of the past disasters that had already occurred. However, there are still gaps in disaster management that need to be filled in, especially given the limited quantity of data that is currently available as a reference for local levels of preparedness. In this study, we dug deeper into the implementation of barangay disaster risk reduction management in barangay San Augustin, Novaliches, and Quezon City. From the results of this study, it was revealed that the majority of the respondents "strongly agree" that the implementation of barangay disaster risk reduction management in barangay San Agustin, Novaliches, Quezon City was implemented in terms of communication and facilities and that some of them "agree" to it in terms of emergency planning. It was also identified that the barangay rarely conducts drills and seminars for its residents on what to do when a disaster occurs. They do not give early warning signals to their residents and basically do not have any emergency plans on hand. The results show the need for active dissemination of the early warning system, for it can help increase resilience by improving one’s capacity to prepare ahead of time, which in turn increases the barangay’s and residents’ abilities to quickly recover and decrease future vulnerabilities. As attested by the overall respondents, the barangay should conduct regular simulation exercises or drills to prepare for the identified primary hazards and risks for disasters. Disasters can happen at any time of the day or in moments that we least expect them to happen, so it is only befitting that the barangay takes care of its residents by equipping them with enough knowledge to reduce or prevent any worst-case scenarios during a disaster.